Destroyed Lung in Children Undergoing Treatment for Pulmonary Tuberculosis: A Case Report - Carissa Aprilia Yusanda; Shinta Nareswari (Medula, 2026)
Tuberculosis (TB) is a global health problem, especially in developing countries, with a high prevalence in South Asia and Sub-Saharan Africa. In 2019, there were around 1.2 million new cases of TB in children and 230,000 deaths from TB in children under 15 years of age. In Indonesia, the incidence of TB is very high, with more than 1 million people diagnosed in 2022, and 140,700 deaths from TB in the same year. One of the serious complications of TB is a destroyed lung, which is an advanced stage of pulmonary TB. This condition causes extensive and progressive damage to the lung parenchyma, disrupts lung function, and has the potential to cause respiratory failure, shortness of breath, secondary infections, and other complications. Although symptoms of TB often appear in the early stages, late diagnosis can worsen the prognosis and increase mortality. This case report analyzes a 13-year-old child patient who was referred to the hospital with complaints of cough, greenish sputum, and coughing up blood after recovering from chickenpox. Radiological examination showed atelectasis, bronchiectasis, and indications of destroyed lung. The diagnosis of pulmonary TB with destroyed lung was obtained after physical examination, laboratory, and other supporting examinations. The management includes treatment with antituberculosis drugs (OAT), antibiotics, supportive therapy, and pulmonary rehabilitation. Appropriate management can improve the patient's quality of life even though the prognosis is poor in the long term.